Emergence of exchange bias field in FeS superconductor with cobalt-doping. (25th June 2021) - Yuan, Peng; Han, Jia; Cheng, Pengyu; Ma, Renhai; Xiao, Qiling; Ge, Jun-Yi; Feng, Zhenjie; Cao, Shixun; Zhang, Jincang; Lu, Wenlai; Chen, Fei
Abstract: Among all the iron-based superconductors, the 11 series has the simplest layered structure but exhibits rich physical phenomenon. In this work, we have synthesized Fe1− x Co x S single crystals with tetragonal structure and studied their structure and magnetic properties. Magnetic susceptibility measurements indicate that the cobalt doping would suppress superconductivity and even introduce weak ferromagnetism besides antiferromagnetism. Scanning electron microscopy study reveals that the Co-doped samples exhibit intrinsic phase separation. Moreover, magnetic force microscopy measurement shows no magnetic domain in Fe1− x Co x S, indicating that neither phase is pure ferromagnetic. The coexistence of ferromagnetism and antiferromagnetism leads to the relatively large exchange bias field. Since the exchange bias effect has been widely used in the field of information storage, spin-valves, and magnetic tunnel junctions, our study provides another option for further application.